IDENTIFIKASI BAKTERI DAN KAPANG PADA PROSES PRE-TREATMENT FESES SAPI POTONG DAN TANDAN KOSONG KELAPA SAWIT - Safitry, Rania Zabina; Marlina, Eulis Tanti; Harlia, Ellin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
The abundance of livestock and agricultural waste needs special attention, especially in its processing. One of the largest wastes generated from the livestock sub-sector is beef cattle feces; in the agricultural sub-sector, empty fruit bunches are produced (EFB). In this study, beef cattle feces and empty fruit bunches were decomposed for 14 days to degrade organic matter into raw materials for second-generation bioethanol. This study aimed to identify bacteria and molds that play a role in the decomposition of beef cattle feces and EFB. The research conducted used a qualitative-descriptive method. This study identified microorganisms in the biological pre-treatment process on days 1st, 7th, and 14th. The identification of bacteria and molds was done macroscopically and microscopically. The genus of bacteria found in biological pre-treatment is Bacillus. There are 3 genera of molds found in biological pre-treatment including Aspergillus, Trichoderma, and Mucor. These genera have cellulotic and lignolytic potential in fiber degradation in biological pre-treatment.